American College Towns as a Road Map for Rural Community Colleges to Imprint Higher Education into Community - Devon Almond (Educational Considerations, 2022)
Rural community colleges are uniquely situated to physically and subtly embed educational imprints into the everyday lives of local people. This reflective article explores how the everyday characteristics of American college towns offer a potential road map for rural community colleges to structure educational imprints into the lifeblood of local towns. This road map is in service of building cultural ecosystems to positively shape the educational trajectories of local people in rural places. Drawing primarily on a multi-year research project that involved physically visiting 100 American college towns, I also draw on campus visits to hundreds of rural community colleges and thousands of small towns across North America to offer ideas related to embedded cultures and rural ways of knowing. The article concludes with specific examples of a few college town characteristics and practical steps for rural community college administrators to embed educational imprints into rural places.
Keywords: Rural community colleges; American college towns; everyday characteristics; embedded cultures; rural community development